The Relationship of Attitudes Towards Food, History of Infectional Diseases, and Family Socio-Economic and Nutritional Status of High School Adolescents - Nor Aida; Mahpolah; Magdalena (Jurnal Riset Pangan dan Gizi, 2025)
Riskesdas South Kalimantan in 2018 reported that in Banjar Regency the prevalence of nutritional status based on BMI/U in adolescents aged 16-18 years had a prevalence of nutritional status that was approximately 15.3% compared to the provincial prevalence of 12.3%. The prevalence of overnutrition also has a higher figure of 14.3% compared to the provincial prevalence of 12.1%. This study aims to determine the relationship between attitudes towards food, history of infectious diseases, and family socioeconomic status with the nutritional status of high school adolescents. This type of research is analytical observational with a cross-sectional design. The population is all students in class X and Research data was taken using a questionnaire. Data analysis used the Spearman Rank correlation test α=0.05. The results of this study showed a positive attitude towards food (52.2%), a history of infectious disease (73.9%), family socioeconomic status ≥ average (55.4%), and good nutritional status (63%). Adolescents are advised to explore more information about nutrition, so that nutritional status can be properly observed, because this study shows that there is no significant relationship between attitudes towards food and nutritional status, there is a significant relationship between a history of infectious diseases and family socio-economic status with the nutritional status of adolescents.